Effectiveness of Gender-Perspective Economic Empowerment Program for Vulnerable Women in Agam Regency in Supporting the Achievement of Sustainable Development Goals - Fitri, Annisa; Sartima, Tarma; Rinawati, Rinawati; Khudri, Nursa’adah (LPPM Universitas Ekasakti, 2024)
The economic empowerment of vulnerable women in Agam Regency is an endeavor aimed at facilitating the realization of the Sustainable Development Goals (SDGs), particularly SDG 5 focusing on gender equality and women's empowerment. Within Agam Regency, vulnerable women encounter a multitude of obstacles such as violence, divorce, poverty, and the consequences of natural calamities, all of which contribute to their state of helplessness. Spearheaded by the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia in partnership with Non-Governmental Organizations (Tabik DC), the empowerment initiative seeks to enhance the capabilities and financial autonomy of vulnerable women through gender-centric entrepreneurship guidance. This research endeavors to evaluate the efficacy of the program and its efficacy in advancing the SDGs. Employing a mixed methods approach, the study encompasses a survey involving 50 vulnerable women from three sub-districts (Baso, Ampek Angkek, Tilatang Kamang). The findings reveal that the program has effectively transformed the mindset of participants while enhancing their entrepreneurial acumen and knowledge in business management. Furthermore, it has played a pivotal role in bolstering self-esteem and financial self-sufficiency among the beneficiaries. By and large, this empowerment scheme significantly contributes to the attainment of the SDGs, notably SDG 5 concerning gender equality and women's empowerment. In conclusion, the economic empowerment program, centered on gender-specific technical guidance in Agam Regency, has triumphed in realizing its objectives of enhancing the capacities and financial autonomy of vulnerable women, thereby aiding in the accomplishment of the SDGs.